Relação família e escola no contexto do ensino fundamental i, na escola municipal Silvino Rodrigues Costa - Silva, Luana Kelly Freitas Ferreira (Universidade Federal do Tocantins, 2020)
The research developed is part of the work of completing the Undergraduate Course in Field Education: Arts and Music, ofthe Federal University of Tocantins, Campus of Tocantinópolis-TO. The research was carried out in the Quatro Bocas community in the municipality of Esperantina-TO, and aimed to verify whether at the Silvino Rodrigues Costa Municipal School there is an active relationship between family and school. As a research problem, the relationship between family and school is established in the context of elementary school I in the Silvino Rodrigues Costa Municipal school, and what are the possible impacts of this articulation on the teaching and learning process? The research is of the case study type, of qualitative approach, and because it is an initial study will be exploratory in nature. The same was systematized through bibliographic review, semi-structured interview. The participants were: teachers, pedagogical coordinator and family members of students linked to the 3rd year and 4th year of elementary school. The research obtained favorable results for education, the objectives proposed in the investigation were achieved, verifying that in school there is a relationship with families, in this case it was possible to know that there is a relationship and it may be able to promote improvements in the teaching and learning process, elements involving the family at school have been identified, which can contribute to education and raise awareness among the parties involved about the importance of the family in the educational process of children.